Diabetic foot wounds: the value of negative pressure wound therapy with instillation - Dalla Paola, Luca (Int Wound J, 2013)
Chronic wounds such as diabetic foot wounds are a tremendous burden to the health care system and often require a multidisciplinary approach to prevent amputations. Advanced technologies such as negative pressure wound therapy (NPWT) and bioengineered tissues have been successfully used in the treatment of these types of complex wounds. However, the introduction of NPWT with instillation (NPWTi) has provided an alternative treatment for treating complex and difficult‐to‐heal wounds. This article provides an overview of NPWT and the new NPWTi system and describes preliminary experience using NPWTi on patients with complicated infected diabetic foot wounds after surgical debridement and in a multidisciplinary setting.